2004
DOI: 10.1080/10428190310001657344
|View full text |Cite
|
Sign up to set email alerts
|

More on Geographic Hematology: The Breakpoint Cluster Regions of the PML/RARα Fusion Gene in Mexican Mestizo Patients with Promyelocytic Leukemia are Different from Those in Caucasians

Abstract: Acute promyelocytic leukemia is characterized the PML/RARalpha chimeric fusion gene, transcript and protein; the breakpoint cluster regions (bcr) in the PML gene may occur in 3 different sites: Intron 6 (bcr1), exon 6 (bcr2) or intron 3 (bcr3). In a 10-year period in a single institution, we studied prospectively the breakpoint cluster regions of the PML/RARalpha fusion gene in 43 Mexican Mestizo patients with APL, and found that the bcr1 represented 62.7%, the bcr2 9.3% whereas the bcr3 27.9%. The prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 5 publications
1
23
0
6
Order By: Relevance
“…The frequency of the breakpoint cluster region 1 (bcr1) PML/RARA isoform was not increased compared with that reported in Europe, which contrasts with previous studies analyzing patients from Latin America. [30][31][32] This difference, however, likely reflects the distinct geographical and ethnic origin of patients in the 2 reported series (eg, Mexican mestizos by Santos et al 28 and mostly Brazilian in this study). Immunofluorescence staining using the anti-PML antibody was adopted as a rapid diagnostic method that could be performed at all centers and did not require a sophisticated infrastructure.…”
Section: Discussionmentioning
confidence: 52%
“…The frequency of the breakpoint cluster region 1 (bcr1) PML/RARA isoform was not increased compared with that reported in Europe, which contrasts with previous studies analyzing patients from Latin America. [30][31][32] This difference, however, likely reflects the distinct geographical and ethnic origin of patients in the 2 reported series (eg, Mexican mestizos by Santos et al 28 and mostly Brazilian in this study). Immunofluorescence staining using the anti-PML antibody was adopted as a rapid diagnostic method that could be performed at all centers and did not require a sophisticated infrastructure.…”
Section: Discussionmentioning
confidence: 52%
“…30 Investigations of 3 breakpoint sites (bcr1, bcr2, and bcr3) of the PML gene involved in APL with t(15;17), have described significantly higher prevalence of bcr1 among individuals from Latin America compared with published reports of non-Latino populations in the United States and Europe. 31,32 In addition, several recent genome-wide association studies of childhood ALL/L have identified risk loci with varying effects by racial/ethnic group for B-and T-cell ALL/L, 33,34 further highlighting the importance of considering disease subtypes according to race/ethnicity and age in etiologic investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Porém, a real incidência da LPA não é conhecida, e a maioria dos estudos baseia-se em registros hospitalares. Existe, ainda, uma variabilidade genética correlacionada à distribuição geográfica, com diferentes freqüências das isoformas do PML-RARα conforme a população estudada [25][26][27] .…”
Section: Epidemiologiaunclassified